Going for the Golgi: small PDI protein helps ATF6 perform better under stress. (22nd July 2019) - Fass, Deborah
Abstract : ATF6 is a major signal transducer for cellular reprogramming in response to protein mis‐folding in the endoplasmic reticulum. However, the mechanism by which ATF6 senses unfolded proteins and becomes activated is not yet known. In this issue of The EMBO Journal, Oka et al show that ERp18, a single‐domain member of the protein disulfide isomerase family, interacts preferentially with ATF6 under stress conditions and regulates ATF6 transport to the Golgi apparatus. Furthermore, ERp18 impacts the ATF6 cleavage product generated in the Golgi, ultimately determining whether or not ATF6 becomes a functional transcription factor and induces the unfolded protein response. Abstract : A new study shows that a small redox‐active protein in the endoplasmic reticulum has a big role to play in the response to unfolded protein stress.